Preoperative Neutrophil-to-Lymphocyte Ratio, Platelet-to-Lymphocyte Ratio, and CEA as the Potential Prognostic Biomarkers for Colorectal Cancer - Fu Ming-Sheng; Du Mei-Ling; Cai Xun-Quan; Hu Yuan-Xin; Zhang Wei-Jie; Pan Qin-Cong (Canadian Journal of Gastroenterology and Hepatology)
Background. This study was to evaluate the prognostic value of the preoperative neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and carcinoembryonic antigen (CEA) in colorectal cancer (CRC) patients and to identify the potential and easily accessible prognostic biomarkers for CRC. Methods. We retrospectively reviewed altogether the records of 330 CRC patients according to inclusion criteria. The clinical characteristics include age at diagnosis, body mass index (BMI), preoperative CEA level, neutrophil , lymphocyte, and platelet count, tumor primary site and size, clinical pathological TNM stage, and survival status were recorded through the review of medical records. The overall survival (OS) was calculated using the Kaplan–Meier method. The Cox proportional hazards model was used for the univariate and multivariate analysis to evaluate the prognostic factors of CRC. Results. A total of 330 patients were finally included in the current study. The mean follow-up duration was 32.8 ± 19.1 months (range, 0.1–67.7). Compared with the median OS, preoperative high NLR, PLR, and CEA, and low BMI had lower median OS. The NLR and PLR value rise indicates lower median OS in stage I-II CRC; however, the NLR value and CEA level rise indicates lower median OS in stage III-IV CRC. Preoperative high NLR, PLR, and CEA level and low BMI have poorer OS by univariate analysis. By multivariate analysis, the age, sex, N, M stage, and BMI demonstrated independently influence the OS of CRC. NLR was an independent predictor of stage I-II CRC, and the CEA level was an independent predictor of stage III-IV CRC. Conclusions. Our results show that preoperative high NLR, PLR, CEA, and low BMI had poorer OS, NLR was an independent predictor of stage I-II CRC, and the CEA level was an independent predictor of stage III-IV CRC.